2017
DOI: 10.1038/cddis.2017.531
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted human p75-positive stem Leydig cells replace disrupted Leydig cells for testosterone production

Abstract: Previous studies have demonstrated that rodent stem Leydig cell (SLC) transplantation can partially restore testosterone production in Leydig cell (LC)-disrupted or senescent animal models, which provides a promising approach for the treatment of hypogonadism. Here, we isolated human SLCs prospectively and explored the potential therapeutic benefits of human SLC transplantation for hypogonadism treatment. In adult human testes, p75 neurotrophin receptor positive (p75+) cells expressed the known SLC marker nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 36 publications
6
52
0
1
Order By: Relevance
“…In contrast, negative control animals that received matrigel alone lacked any ALCs. The presence of differentiation in LCs in autografts was confirmed by immunofluorescence (IF) which stained ALCs positively for 3BHSD, STAR, and LHR (marker of LC) (Fig. D).…”
Section: Resultsmentioning
confidence: 82%
“…In contrast, negative control animals that received matrigel alone lacked any ALCs. The presence of differentiation in LCs in autografts was confirmed by immunofluorescence (IF) which stained ALCs positively for 3BHSD, STAR, and LHR (marker of LC) (Fig. D).…”
Section: Resultsmentioning
confidence: 82%
“…As unlicensed substances they are applied as performance-enhancing substances and for doping. Ultimately, for ideal substitution hope rests on human stem Leydig cells transplanted to hypogonadal patients (84). The goal for these patients -at least those with an intact hypothalamo-pituitary system -would be that the testosterone production required would be provided by the transplanted Leydig cells and would be self-regulated by feedback to LH.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that SLCs are multipotent stem cells and can differentiate into adipocytes. 24 We performed a Figure 8A). We used qPCR to confirm the mRNA levels of these genes (Dlk1, Fabp4 and Lpl) and Western blotting to measure the protein levels of their products.…”
Section: Fhf1 Prevents the Transition Of Stem Cells Into Adipocyte mentioning
confidence: 99%